Impact of safety measures for hazard recognition on the rate of accidents on construction sites in Abuja, Nigeria - Shittu, Abdullateef Adewale; Popoola, Kudirat; Tsado, Abel John; Shehu, Muhammad Aminu; Abdulazeez, Shakirat Remilekun (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study evaluated the impact of safety measures for hazard recognition on the rate of accidents on construction sites in Abuja, Nigeria. A survey design was adopted through a quantitative study with the use of questionnaire for collecting data from 25 construction firms registered with Federation of Construction Industry in Abuja. Analysis of data was undertaken using Relative Importance Index (RII) and Mean Item Score (MIS). Findings from the study revealed that the most important safety measures for hazard recognition required for improving the safety performance of construction firms in Abuja is Conducting safety meetings (RII = 0.96); the most significant influence of safety measures for hazard recognition on the frequency of occurrence of accidents is Improvement of employees’ and employers’ safety behaviour (MIS = 4.38); and the most effective strategy for reducing the rate of accidents on construction sites is Management commitment (MIS = 4.57). It was thus concluded that the safety measures for hazard recognition have significant impact on the rate of accidents on construction sites in Abuja. It was recommended that construction firms should set up a mechanism for the effective implementation of the safety measures for hazard recognition.